Accrual-Based Accountability Of Budgeting Realization Report In A Government Institution - Eko Setiawan; Ahmad Juanda; Driana Leniwati (UNIVERSITAS PAKUAN, 2025)
Government agencies are the primary target for achieving this. Essentially, every aspiration, particularly those related to material or financial matters, will be crucial in the implementation of good governance. This research aims to understand its application related to the theory of new institutional analysis. Methods, Data collection techniques include interviews and observation methods. This interview is used as a data collection technique when the researcher wants to conduct a preliminary study to identify a problem that requires further investigation. The object of this research is the Megang Sakti District Office in Musi Rawas Regency. Result. Due to the insistence on legal products, it is encouraged to make changes in information technology. The phenomenon that occurs indicates the presence of special symptoms, namely coercive isomorphism and normative isomorphism. This can pose challenges such as the need for resources and technology systems, requiring changes to accounting systems, staff training, and investment in supporting accounting software. The complexity of Transaction Management requires significant changes in the process of recording transactions and making adjustment journals. Implementation. Implementation of accrual-based accountability and government institutions